PENGARUH KUALITAS DAN CITRA MEREK TERHADAP KEPERCAYAAN DAN DAMPAKNYA TERHADAP MINAT BELI PRODUK PRIVATE LABEL INDOMARET (STUDI KASUS PADA KONSUMEN INDOMARET DI YOGYAKARTA) - Wijayanti Marhaeni; Ignatius Soni Kurniawan (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
Effect of quality and brand image of Indomaret product private label on purchase intention with trust as intervening variable: A case study of Indomaret in Yogyakarta.A study has been conducted to investigate the effect of quality and brand image of Indomaret product private label on purchase intention of Indomaret customers in Yogyakarta with trust as intervening variable.The sample consists of 100 Indomaret customers in Yogyakarta.brand image are positively correlated with trust. Furthermore, quality and brand image are positively correlated with purchase intention.Quality, brand image and trust are simultaneously positively correlated with purchase intention.Keyword : quality,brand image,trust, purchase intention